SISTEM PEMESANAN TIKET BUS ONLINE PADA BANDARA UDARA DI MEDAN BERBASIS ANDROID - Bryan Bryan; Jhon Edwin Manurung; Ramadani Nasution (Politeknik Bisnis Indonesia, 2019)
The development of information technology has been widely used by all companies to improve service to the community. The use of information technology in a company is of course adapted to the needs of the system design in the company. Technology is no longer seen as a complement, but has become a necessity for the implementation of goals and strategies of the company. The developing technology is certainly very necessary to be applied in the business processes that exist in airport companies. Airports, especially in Medan, usually provide bus services to take airport passengers who will return home. The process of ordering these bus services is usually done conventionally, which is quite troublesome because passengers have to queue and go to the ticket sales counter first. In addition, conventional ticket reservations cannot make a choice of seat position to be occupied. Based on these problems, a mobile-based application will be built to enable passengers to order tickets and choose seats online. In the process of developing an information system using the Laravel framework and the Java programming language. From the results of this study, an online bus ticket booking application system was obtained at the airport company.